Geometric factors influencing the diet of vertebrate predators in marine and terrestrial environments. (30th September 2014) - Carbone, Chris; Codron, Daryl; Scofield, Conrad; Clauss, Marcus; Bielby, Jon; Enquist, Brian
Abstract Predator–prey relationships are vital to ecosystem function and there is a need for greater predictive understanding of these interactions. We develop a geometric foraging model predicting minimum prey size scaling in marine and terrestrial vertebrate predators taking into account habitat dimensionality and biological traits. Our model predicts positive predator–prey size relationships on land but negative relationships in the sea. To test the model, we compiled data on diets of 794 predators (mammals, snakes, sharks and rays). Consistent with predictions, both terrestrial endotherm and ectotherm predators have significantly positive predator–prey size relationships. Marine predators, however, exhibit greater variation. Some of the largest predators specialise on small invertebrates while others are large vertebrate specialists. Prey–predator mass ratios were generally higher for ectothermic than endothermic predators, although dietary patterns were similar. Model‐based simulations of predator–prey relationships were consistent with observed relationships, suggesting that our approach provides insights into both trends and diversity in predator–prey interactions.